Invited examiner of PhD dissertations : Giammarco Giovanetti (Univesity of Ancona), Distant external examiner of the dissertation Title: A new strawberry (Fragaria x ananassa) breeding program to advance critical steps and obtain new resilient and high-quality cultivars Advisors: Bruno Mezzetti, Franco Capocasa Almenar - Manganaris, George A. (My University, 2026)
Invited examiner of PhD dissertations.
Keywords: Sciences